2016
DOI: 10.1159/000452416
|View full text |Cite
|
Sign up to set email alerts
|

Positive Traits in the Bipolar Spectrum: The Space between Madness and Genius

Abstract: Bipolar disorder is a severe, lifelong mood disorder for which little is currently understood of the genetic mechanisms underlying risk. By examining related dimensional phenotypes, we may further our understanding of the disorder. Creativity has a historical connection with the bipolar spectrum and is particularly enhanced among unaffected first-degree relatives and those with bipolar spectrum traits. This suggests that some aspects of the bipolar spectrum may confer advantages, while more severe expressions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 220 publications
(277 reference statements)
0
23
0
3
Order By: Relevance
“…It has long been suggested and accepted that BD and mania are associated with increased forms of creativity (Greenwood, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has long been suggested and accepted that BD and mania are associated with increased forms of creativity (Greenwood, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has long been suggested and accepted that BD and mania are associated with increased forms of creativity (Greenwood, 2016 ). Hypomania (a mild form of mania) is positively correlated with a fluency of divergent thinking (Furnham, Batey, Anand, & Manfield, 2008 ), which is the most typical measure of creativity in the laboratory setting.…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention has been given to the question of how temperament and bipolar diathesis interact with creativity [37][38][39][40][41]. This interaction is interesting in both directions, as music can be used to express psychopathology [21,42] and as musicians can be affected by psychiatric disorders [42].…”
Section: Temperament Creativity and The Bipolar Spectrummentioning
confidence: 99%
“…Earlier family and twin studies indicated a pivotal role of genetic factors in the etiology of mood disorders 3 – 6 ; however, the specific modes of inheritance have been found to be complex and polygenic 7 – 10 . In brief, while BPD and MDD differ from each other in age of onset, clinical presentation, and treatment response 11 , they still share several specific clinical features such as the presence of depressive episodes, mood instability and impaired cognition. Moreover, meta-analyses of family studies have found elevated rates of BPD in first-degree relatives of MDD patients and vice versa 12 .…”
Section: Introductionmentioning
confidence: 99%